2021
DOI: 10.14260/jemds/2021/301
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Shear Bond Strength of Packable Glass Ionomer Cement, Resin Modified Glass Ionomer Cement, Compomer and Giomer to Primary and Permanent Teeth - An In Vitro Study

Abstract: BACKGROUND With the changing demand in dentistry, a wide range of dental materials is present in the market today. Choosing the best material for a given situation becomes confusing for a clinician. Shear bond strength gives an idea of retentiveness of a material partially. The purpose of the study was to determine and compare shear bond strength (SBS) of packable glass ionomer cement (GIC), resin- modified glass ionomer cement (RMGIC), compomer, and giomer to primary and permanent teeth. METHODS An in-vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Carvalho et al also evaluated the shear bond strength of conventional GICs and concluded their mean values to be lower [18] . Singh et al determined from their study that composite resin (16.21 ± 1.12) had the highest shear bond strength value while lowest was conventional GIC (2.94 ± 0.91) [14] . In accordance with the results of our study, the results of the in vitro studies conducted by Mallya et al and Verma et al suggested mechanical properties of Cention N were significantly higher as compared to that of GIC Type IX [19,20] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Carvalho et al also evaluated the shear bond strength of conventional GICs and concluded their mean values to be lower [18] . Singh et al determined from their study that composite resin (16.21 ± 1.12) had the highest shear bond strength value while lowest was conventional GIC (2.94 ± 0.91) [14] . In accordance with the results of our study, the results of the in vitro studies conducted by Mallya et al and Verma et al suggested mechanical properties of Cention N were significantly higher as compared to that of GIC Type IX [19,20] .…”
Section: Discussionmentioning
confidence: 98%
“…To anticipate the thermal changes involved in a possible real oral cavity, two in vitro aging strategies were implemented. First the samples were immersed in distilled water for 7-10 days since alterations of the substrate caused by storage solutions can affect bond strength [14] . Second was the use of thermocycling ageing, where specimens are immersed in water baths at different temperatures between standardized intervals of time [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Calvo et al (34) are in agreement with the present results and claim that 80% of glass ionomer cements showed an adhesive mode of failure. However, a study by Singh et al (35) revealed that the mode of failure of glass ionomer cements mostly mixed (cohesive inside the material), implying that the obtained outcomes didn't reflect the strength of the bonded interface but rather the material's intrinsic weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Dental practitioners have also been confronted Since the beginning of dental practice, people have struggled with this issue, and a bigger portion of dental science is still devoted to finding artificial materials that can replace missing tooth structure. 1 Oral health is a critical aspect of general health since it helps to maintain the wellbeing of the craniofacial complex, teeth apparatus, as well as the orofacial tissues that surround the mouth on the face and head. 2,3 Dentin and enamel demineralize as a result of dental caries, a chronic disorder that affects teeth and is brought on by organic acids produced by bacterial fermentation of carbohydrates.…”
Section: Introductionmentioning
confidence: 99%